สารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ กองทันตสาธารณสุข สำนักอนามัย กรุงเทพมหานคร (BALANCED SCORECARD QUALITY INFORMATION FOR THE DENTIST DEVELOPMENT IN DENTAL HEALTH DIVISION, HEALTH DEPARTMENT, BANGKOK METROPOLITAN ADMINISTRATION) - Boonyathada, Thitikorn; Chookittikul, Jaruek; Chookittikul, Wajee; Nuttee, Cholwich (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2013)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1) วิเคราะห์และออกแบบสารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ สำหรับผู้เกี่ยวข้อง 2) ศึกษาการยอมรับของผู้เกี่ยวข้องที่มีต่อสารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ 3) ศึกษาความต้องการใช้งานของผู้เกี่ยวข้องที่มีต่อสารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ ตัวอย่างผู้เกี่ยวข้องในการวิจัยนี้เป็นผู้บริหาร 3 ระดับ คือ ระดับปฏิบัติการ ระดับการจัดการและระดับยุทธศาสตร์ สังกัดกองทันตสาธารณสุข สำนักอนามัย กรุงเทพมหานคร จำนวน 41 คน ซึ่งใช้วิธีการเลือกสองแบบ คือ แบบเจาะจงและแบบไม่เจาะจงโดยใช้ตารางเลขสุ่มจากประชากร จำนวน 80 คน เครื่องมือที่ใช้ในการวิจัยนี้ คือ 1) สารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ จำนวน 50 ฉบับ 2) แบบประเมินการยอมรับและแบบประเมินความต้องการใช้งานสารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ สถิติที่ใช้ในการทดสอบสมมุติฐาน คือ การทดสอบไค-สแควร์ ผลการวิจัยพบว่า สารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ กองทันตสาธารณสุข สำนักอนามัย กรุงเทพมหานคร ที่ผู้วิจัยวิเคราะห์และออกแบบได้รับการยอมรับในระดับมากและมีความต้องการใช้งานจากผู้เกี่ยวข้องทั้งสามระดับ จำนวน 44 ฉบับ โดยผู้ให้การยอมรับมีจำนวนมากกว่าผู้ไม่ให้การยอมรับอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 คำสำคัญ: สารสนเทศคุณภาพบาล้านซ์สกอร์ค้าร์ดเพื่อการพัฒนาทันตแพทย์ คิวไอที การยอมรับ This research aimed to 1) analyze and design the Balanced Scorecard Quality Information for the Dentist Development in Dental Health Division, Health Department, Bangkok Metropolitan Administration for the stakeholders and 2) study the acceptance of the stakeholders on the Balanced Scorecard Quality Information for the Dentist Development. 3) study the need to use of the stakeholders on the Balanced Scorecard Quality Information for the Dentist Development. The samples were selected from 3 management levels of the Dental Health Division, Health Department, Bangkok Metropolitan Administration which were operating level, managerial level and strategic level. Forty one samples were selected from eighty populations by the purposive and the random sampling using the random number table. The research tools were 1) fifty copies of Balanced Scorecard Quality Information for the Dentist Development. and 2) acceptance evaluation and usage need evaluation form. The statistics used for hypothesis testing was the Chi-square test. The results of this research found that forty four copies of the Balanced Scorecard Quality Information for the Dentist Development analyzed and designed by the researcher were accepted and needed to use by the 3 levels of the stakeholders. The number of acceptors were higher than the number of deniers with the statistical significant level at 0.05. Keywords: Balanced Scorecard Quality Information for the Dentist Development, QIT (Quality Information Technology), Acceptance